Solar Wind Induced Waves in the Skies of Mars: Ionospheric Compression, Energization, and Escape Resulting From the Impact of Ultralow Frequency Magnetosonic Waves Generated Upstream of the Martian Bow Shock. Issue 9 (28th September 2018) - Collinson, Glyn; Wilson, Lynn B.; Omidi, Nick; Sibeck, David; Espley, Jared; Fowler, Christopher M.; Mitchell, David; Grebowsky, Joseph; Mazelle, Christian; Ruhunusiri, Suranga; Halekas, Jasper; Frahm, Rudy; et al.
Abstract: Using data from the National Aeronautics and Space Administration Mars Atmosphere and Voltatile EvolutioN and the European Space Agency Mars Express spacecraft, we show that transient phenomena in the foreshock and solar wind can directly inject energy into the ionosphere of Mars. We demonstrate that the impact of compressive ultralow frequency waves in the solar wind on the induced magnetospheres drive compressional, linearly polarized, magnetosonic ultralow frequency waves in the ionosphere, and a localized electromagnetic "ringing" at the local proton gyrofrequency. The pulsations heat and energize ionospheric plasmas. A preliminary survey of events shows that no special upstream conditions are required in the interplanetary magnetic field or solar wind. Elevated ion densities and temperatures in the solar wind near to Mars are consistent with the presence of an additional population of Martian ions, leading to ion‐ion instablities, associated wave‐particle interactions, and heating of the solar wind. The phenomenon was found to be seasonal, occurring when Mars is near perihelion. Finally, we present simultaneous multipoint observations of the phenomenon, with the Mars Express observing the waves upstream, and Mars Atmosphere and Voltatile EvolutioN observing the response in the ionosphere. When these new observations are combined with decades of previous studies, they collectively provide strong evidence for a previously undemonstrated atmospheric loss process at unmagnetized planets: ionospheric escape driven by the direct impact of transient phenomena from the foreshock and solar wind. Key Points: The impact of ultralow frequency (ULF) waves in the solar wind can drive compressional magnetosonic ULF waves in the ionosphere of Mars We survey MAVEN data, plus examine simultaneous multipoint observations by Mars Express, finding this phenomena occurs at Martian perihelion These ionospheric ULF waves drive compressive heating of the ionosphere and launch bursts of time‐dispersed energetic ions